An evaluation of outcrossing to improve mass-reared strains of the Queensland fruit fly Bactrocera tryoni. (19th August 2014) - Gilchrist, A.S.; Meats, A.W.
Abstract : Outcrossing to wild or unrelated strains has been proposed as a counter to the negative effects of adaptation by domesticated animals to captive-breeding environments. However, for mass-reared insects intended for sterile insect technique release, outcrossing may reduce productivity in mass-rearing facilities. In this study, we characterized adaptation to mass-rearing in the Queensland fruit fly Bactrocera tryoni (Froggatt). The features of domesticated B. tryoni were similar to those of other domesticated tephritids: shortened preoviposition period, higher egg production and increased early survival. We also examined the practical use of outcrossing to improve mass-reared strains. The B. tryoni mass-reared strain was crossed with independent strains that had already been domesticated for a varying number of generations. Preoviposition period, egg production, survival and stress tolerance were measured in the resulting hybridized strains. The short preoviposition period of the mass-reared strain was retained in outcrossed flies, indicating a genetically dominant trait. Egg production in outcrossed flies exceeded the mid-parent value, indicating some hybrid vigour for this trait. If both parents exhibited high egg production, the egg production of outcrossed strains was as high as that of the mass-reared strain. The high early survival of domesticated tephritids was reduced in outcrossed females, but not in outcrossed males. Preliminary thermal stress tests revealed that outbred flies were more stress resistant than the mass-reared strain. Therefore, the anticipated loss of productivity in outcrossed B. tryoni mass-reared strains is avoidable by choosing suitable parental strains and the outcrossed flies should have improved field performance. Using already domesticated strains should also facilitate the annual renewal of hybrid strains.